PENGARUH KOMUNIKASI, MOTIVASI KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI PADA SUB BAGIAN UMUM DAN PENGADAAN KEMENTERIAN PERTANIAN RI - Siti Maulita (2021)
This study uses quantitative research with the aim of knowing and proving the effect of communication on employees performance at the Sub-Section of General and Procurement of the Agriculture Ministry RI, knowing and proving the effect of work motivation on employees performance at the Sub-Section of General and Procurement of the Agriculture Ministry RI, knowing and proving the influence between physical work environment on employee performance at the Sub-Section of General and Procurement of the Agriculture Ministry RI. This study uses primary data, and the research method involves two variables: the dependent variable (employee performance) and the independent variable (communication, work motivation and physical work environment). The population there are as many as 230 employees and the sample used in this study is 86 people. The sampling technique used is the Nonprobability Sampling technique using Sampling Insidental. The analysis used is the mean, validity test, reliability test, coefficient of determination (R2), t test. The results of the study: communication, work motivation and physical work environment partially affect employees performance at the Sub-Section of General and Procurement of the Agriculture Ministry RI.